Beasts of burden wise dogs and eldritch men - Dorkin, Evan 1965-; Piekos, Nate (Beasts of burden, 2019)
"A heroic pack of canines known as the Wise Dogs sets off on a mission to clean up a Pennsylvania corridor plagued by seemingly unrelated occult disturbances that include a fire salamander and a horde of mutant lurkers. A link is found among the various disturbances, leading our heroes to a mountain village inhabited by a survivalist witch-cult"...